Voice onset time in Spanish–English spontaneous code-switching. (September 2015) - Piccinini, Page; Arvaniti, Amalia
Abstract: Research on the phonetics of code-switching has focused on voice onset time (VOT) and has yielded mixed results regarding cross-language interaction, possibly due to differences in data used (scripted vs. spontaneous speech) and populations examined (L1 vs. L2 dominant, early vs. late bilinguals). Here VOT was measured in a corpus of spontaneous code-switching speech elicited from a homogeneous group of early bilinguals in conversation with and without distraction (completion of jigsaw puzzles). The distraction meant to increase cognitive load, a manipulation that could affect phonetic realization. Both English and Spanish VOT were shorter at code-switching points than in comparable monolingual utterances. English VOT lengthened overall under increased cognitive load (but remained shorter in code-switching as compared to the monolingual context). These results support previous findings of VOT shortening in code-switching for both English and Spanish, and confirm that the effect applies in the natural speech of early bilinguals. Highlights: We examine voice onset time in spontaneous Spanish–English code-switching. We examine effects of increased cognitive load on voice onset time duration. In both English and Spanish, VOT in code-switching contexts became shorter. In English, VOT became longer when cognitive load was increased. Supports past findings, with a homogeneous population producing spontaneous speech.